2019
DOI: 10.1002/ppul.24436
|View full text |Cite
|
Sign up to set email alerts
|

Metered‐dose inhaler therapy with spacers: Are newborns capable of using this system correctly?

Abstract: Introduction: Aerosol therapy using a metered‐dose inhaler (MDI) coupled to a spacer chamber is the most widely used long‐term treatment modality for chronic lung disease of prematurity. However, its use in neonates is based on data obtained from other age groups. Proper use of maintenance treatment is essential for the long‐term stability of these patients. Objective: To ascertain whether newborns are capable of generating negative pressure during the use of a spacer with face mask for aerosol therapy. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…There is little evidence regarding the necessary skills or the optimal age for transitioning children from the mask‐plus‐VHC concept to a mouthpiece‐plus‐VHC concept 24 . Herbes et al analysed MDI therapy with a VHC and face mask in 117 low‐risk newborns and showed that only 37% were able to generate a sufficient negative pressure to open the chamber valve 25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little evidence regarding the necessary skills or the optimal age for transitioning children from the mask‐plus‐VHC concept to a mouthpiece‐plus‐VHC concept 24 . Herbes et al analysed MDI therapy with a VHC and face mask in 117 low‐risk newborns and showed that only 37% were able to generate a sufficient negative pressure to open the chamber valve 25 …”
Section: Resultsmentioning
confidence: 99%
“…24 Herbes et al analysed MDI therapy with a VHC and face mask in 117 low-risk newborns and showed that only 37% were able to generate a sufficient negative pressure to open the chamber valve. 25 Iramain et al demonstrated in 103 children (aged 2-14 years) who were admitted to the emergency room with a severe acute exacerbation of asthma, that administration of salbutamol/ipratropium by MDI with VHC and face mask was more effective than a nebulizer therapy. 26 Snider et al analysed 890 patients (aged 2-17 years) with mild to moderate asthma exacerbations and demonstrated the non-inferiority of MDI albuterol therapy compared to breath-actuated albuterol nebulizer therapy.…”
Section: Paediatric Patients-problems and Solutionsmentioning
confidence: 99%
“…Reginato et al 27 showed that approximately 20% of infants under 2 years of age were unable to open the one‐way valve of various VHCs during their inspiratory cycles. Herbes et al 28 found that more than half of the newborns were unable to generate an inspiratory flow capable of opening the one‐way valve of a VHC, even when using an appropriate VHC and face mask. Therefore we would suggest observing the movement of the valves first.…”
Section: Discussionmentioning
confidence: 99%
“…Herbes et al studied this in neonates at 12-48 hours of life and found that most are not capable of generating the negative inspiratory force required to open the one-way valve of a holding chamber. 36 It should be noted, however, that older infants were not studied so this may not apply in those children.…”
Section: Asthma Managementmentioning
confidence: 99%
“…While there is good evidence that MDIs with a holding chamber work well in older children, there has been debate as to whether or not infants can use them effectively. Herbes et al studied this in neonates at 12–48 hours of life and found that most are not capable of generating the negative inspiratory force required to open the one‐way valve of a holding chamber 36 . It should be noted, however, that older infants were not studied so this may not apply in those children.…”
Section: Asthma Managementmentioning
confidence: 99%